Il teatro di Edna Mazya: dal dramma famigliare a quello storico-politico (Altre Modernità, 2011)
A macroscopic trend in contemporary Israeli literature concerns the growing success and increase of women writers. Even in theatre - a genre which, in current Jewish culture, is new in many aspects -, many women dramatists are gaining considerable achievements. The incidence of this phenomenon may be valued in the light of some innovative contributions, such as the elaboration of various female - or feminist - themes. The dramatic writings of Edna Mazya are particularly eloquent if read according to this analysis. In this article we will deal with some of her literary topics, which recur especially in her drama Herod (May 2000): on the one hand, the biblical inspiration and the actualization of biblical features and Mazya's leitmotif, i.e. the representation of marginalized characters and their stories in contrast to the “main stream”.